Cross-border liquidity, relationships and monetary policy: Evidence from the Euro area interbank crisis - Puriya Abbassi; Falk Bräuning; Falko Fecht; José-Luis Peydró (Deutsche Bundesbank, 2014)
We analyze the impact of financial crises and monetary policy on the supply of wholesale funding liquidity, and also on the compositional supply effects through cross-border and relationship lending. For empirical identification, we draw on the proprietary bank-to-bank European interbank dataset extracted from Target2 and also exploit the Lehman and sovereign crisis shocks as well as the main Eurosystem non-standard monetary policy measures. The robust results imply that the crisis shocks lead to worse access, volumes and spreads (in both the overnight and longer-term maturities). The quantitative impact on interbank access and volume is stronger than on spreads. Liquidity supply restrictions are exacerbated for cross- border lending after the Lehman failure; for banks headquartered in periphery countries, the impact is quantitatively stronger in the sovereign debt crisis. Moreover, the interbank market - unlike other credit markets - allows to exploit the price dispersion from different lenders on identical credit contracts, i.e. overnight uncollateralized loans in the same morning for the same borrower. This price dispersion increases massively with the crisis, and even more for riskier borrowers. Cross-border and previous relationship lenders charge higher prices for identical contracts in the crisis. Importantly, this price dispersion substantially decreases when the Eurosystem promises unlimited access to liquidity at a fixed price in October 2008 and announces the 3-year LTRO in December 2011, with economically stronger effects for borrowers in weaker countries.
Keywords: E44; E58; G01; G21; G28; 330; interbank liquidity; financial crises; monetary policy; credit supply; credit rationing; information asymmetry; euro area; financial globalization